High-resolution acoustophoretic 3D cell patterning to construct functional collateral cylindroids for ischemia therapy. Issue 1 (December 2018) - Kang, Byungjun; Shin, Jisoo; Park, Hyun-Ji; Rhyou, Chanryeol; Kang, Donyoung; Lee, Shin-Jeong; Yoon, Young-sup; Cho, Seung-Woo; Lee, Hyungsuk
Abstract The fabrication of functional tissues is essential for clinical applications such as disease treatment and drug discovery. Recent studies have revealed that the mechanical environments of tissues, determined by geometric cell patterns, material composition, or mechanical properties, play critical roles in ensuring proper tissue function. Here, we propose an acoustophoretic technique using surface acoustic waves to fabricate therapeutic vascular tissue containing a three-dimensional collateral distribution of vessels. Co-aligned human umbilical vein endothelial cells and human adipose stem cells that are arranged in a biodegradable catechol-conjugated hyaluronic acid hydrogel exhibit enhanced cell-cell contacts, gene expression, and secretion of angiogenic and anti-inflammatory paracrine factors. The therapeutic effects of the fabricated vessel constructs are demonstrated in experiments using an ischemia mouse model by exhibiting the remarkable recovery of damaged tissue. Our study can be referenced to fabricate various types of artificial tissues that mimic the original functions as well as structures. Engineering 3D tissues faces the challenge of adequate vascularisation for nutrient delivery and gas exchange deep inside the construct. Here the authors use surface acoustic waves to create an aligned array of blood vessels in a hyaluronic acid hydrogel and use it to improve function in a mouse hindlimb ischemia model.